Definição e abordagem de currículo: exame de um curso de formação de professores para a educação não formal em ONGs - Perez, Deivis [UNESP] (Universidade Federal de Santa Maria, 2014)
This article presents a research aimed to analyze the approach and the definition of guiding curriculum of teacher training for work in the non-formal education in non-governmental organizations (NGOs). We opted for a qualitative approach and case study of Te- acher Training Course for NGOs, developed by Ong São Paulo-SP. The research instruments were: analysis of documents of the cou- rse, interviews with trainers and coordinator and literature review. In this course, curriculum is defined as a path to be followed by students and instructors and the coordinator of the subjects studied. We adopted the so-called Integrated Curriculum, in which teaching occurs by the study of problem situations and integrators of learning projects. At the end, we suggest improving the course and following that information, it is hoped, one will support the production of fur- ther comparative research.

Este artigo apresenta pesquisa cujo objetivo foi analisar a definição e abordagem de currículo norteadores da formação de professores para o trabalho na educação não formal em organizações não governamentais (Ongs). Optou-se pela perspectiva qualitativa de pesquisa e estudo de caso do curso Formação de Professores para Ongs, desenvolvido por Ong de São Paulo-SP. Os instrumentos de pesquisa foram: análise dos documentos do curso, entrevistas semidiretivas com formadores e coordenador e revisão da literatura. Nesse curso define-se currículo como caminho a ser percorrido por alunos e formadores e como organizador das temáticas estudadas. Adota-se abordagem nomeada Currículo Integrado, em que o ensino ocorre pelo estudo de situações-problema e projetos integradores das aprendizagens. Ao final, sugere-se aperfeiçoamento do curso e seguem informações que, espera-se, apoiem a produção ulterior de pesquisas comparativas.
Definition of curriculum and approach: study of a training course for teachers of non-formal education in NGOs
Keywords: Curriculum; Teacher training; Non-formal education; Currículo; Educação não formal; Formação de professores